Echoes of Resistance : The role of storytelling and performing arts in preserving Palestinian identity - Edelbi, Khitam; Almanal Timraz, Shams (Education & Theatre, 2025)
This article examines the central role of the native voice in transmitting historical memory, emphasising how it sustains collective identity and shapes our vision of the future. In the Palestinian context, storytelling serves as both a cultural archive and an act of resistance, countering fragmentation by maintaining narrative continuity. The analysis engages with embodied art forms such as dabkeh, theatre, literature and mural painting on the separation wall as vital modes of cultural expression and political testimony. The legacy of Ghassan Kanafani is highlighted, recognising his assertion that storytelling is a form of cultural survival and a revolutionary act. Contributions by Khitam Edelbi and Shams Almanal Timraz further ground the discussion. The first is a narrative recounted by Muhibah Edelbi and the second is a performance by Sabha Timraz. Both recount intergenerational memories of displacement from Al-Birwa and Isdud during the Nakba of 1948. These stories serve as a form of mnemonic resistance against erasure. Finally, the article examines the role of graffiti during the First and Second Intifadas, as well as how Palestinian narratives have gained a wider reach through theatre and digital media. These continue to amplify marginalised voices across global platforms.